A semiotic visual discourse gender study of feminine representations in Cosmopolitan Magazine's visual images - Bonifacio, Stephen Gil 1984-
"this study expands on research gender representations in the media specifically the representations of women in the Philippine media. A structuralist semiotic framework was used to deconstruct visual images in Cosmopolitan Philippines to gauge female representations in women's magazines. Structural deconstruction of the images found out the feminine standards propagated by this magazine: The modern woman is beautiful, sexy, fashionable, strong and independent among others. For a women's magazine, the publication seems to rely heavily on masculine subjects to properly convey their messages. In the visual images studies, women subjects, with a few exceptions are always accompanied by male subjects. Women's identities seem to be shaped in her relation to men. The importance of outward appearance in a woman's life was also highlighted in the images. A survey of the women readers of the magazine showed that this code of femininity is shared by its readers. This hegemonic code serves as the society's feminine standard creating subject positions wehre women can negotiate her identity."